Model Integratif Manajemen SDM dan Digitalisasi Kesehatan Lingkungan Sekolah dalam Pendampingan Keberlanjutan TdBA di SDN 5 Nagrikaler - Mardiman; Deni Maulana Suwanta; Agan Syahrial; Rani Hendiyani; Abd Ghofar; Irwin Dwinanto; Eka Yuni Nur Jannah; Muhammad Fathurrahman; Isma Muslihati Saleha; Stevany Destiyana (Yayasan Vifada Cendikia Indonesia, 2026)
The Tatanen di Bale Atikan (TdBA) Program at SDN 5 Nagrikaler faces sustainability challenges due to weak human resource (HR) management and the absence of a data-based monitoring system for school environmental health practices. To address these issues, a three-day Community Service program was conducted, developing an integrative model that combines competency-based TdBA HR management and environmental health digitalization through a dashboard built on Google Form and Google Data Studio. The method used was participatory mentoring with a Pancaniti approach (from Niti Harti to Niti Sajati). The results show significant improvement: active teacher participation increased from 42% to 85%, activity documentation frequency rose from 1.2 to 4.7 times, and the volume of composted organic waste increased from 3.5 to 6.8 kg per week. Furthermore, TdBA practices have begun to be internalized as part of the school culture, as seen in changes in student behavior and school canteen practices. Digital tools not only function as monitoring instruments but also strengthen accountability and collective participation. This model has proven to be realistic, adaptable, and holds potential for replication in other rural schools. Keywords: Management, Environmental Health Digitalization, Tatanen di Bale Atikan, Purwakarta, Pancawaluya.